2012
DOI: 10.1016/j.fbp.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drying and pretreatment on the nutritional and functional quality of raisins

Abstract: Table 1. Mean values of water activity and main compounds in the Thompson 2 seedless grape variety before and after each drying treatment. In parenthesis is the 3 standard deviation. 4 5 Table 2. Mean values of water activity and main compounds in the Imperial 6Seedless variety before and after each drying treatment. In parenthesis is the 7 standard deviation. 8 9 Table 3. Mean values of water activity and main compounds (referred to fresh 10 fruit mass) of the two varieties of grapes dried by the two drying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 28 publications
5
39
1
6
Order By: Relevance
“…The effects of drying treatments on the phenolic compounds of foods have been studied before. Some previous studies showed that heat treatment is very effective for increasing the total phenolic content in different foods, such as dried apricots (Sultana et al, 2012), tomatoes (Chang et al, 2006) and raisins (Carranza-Concha et al, 2012). Although some authors (Zanoelo et al, 2006;Sultana et al, 2012) note that total phenolics decrease during thermal processing of foods, others (Dewanto et al, 2002) have reported no significant changes.…”
Section: Total Phenolic Contentmentioning
confidence: 91%
“…The effects of drying treatments on the phenolic compounds of foods have been studied before. Some previous studies showed that heat treatment is very effective for increasing the total phenolic content in different foods, such as dried apricots (Sultana et al, 2012), tomatoes (Chang et al, 2006) and raisins (Carranza-Concha et al, 2012). Although some authors (Zanoelo et al, 2006;Sultana et al, 2012) note that total phenolics decrease during thermal processing of foods, others (Dewanto et al, 2002) have reported no significant changes.…”
Section: Total Phenolic Contentmentioning
confidence: 91%
“…The influences of drying techniques on the phenolic compounds of foods were inspected before. Some of these studies had shown that heat treatment is very practical for raising the TPC in various food samples such as dry raisins (Carranza-Concha et al, 2012), apricots (Sultana et al, 2012) and orange peels (Chen et al, 2011). Additionally, some results pointed that microwave technique raised the TPC considerably in pepper, broccoli, green beans (Turkmen et al, 2005) and barley (Gallegos-Infante et al, 2010).…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…Diferentes tipos de pré-tratamento químico são utilizados para conferir a quebra da impermeabilidade da casca da uva, estas são comumente imersas em soluções que contêm hidróxido de sódio (NaOH) (CARRANZA-CONCHA et al, 2012), carbonato de potássio (K 2 CO 3 ) (BINGOL et al, 2012) e carbonato de cálcio (CaCO 3 ) (GABAS et al, 1999). Porém, além de notar-se o benefício da aplicação dessas substâncias com relação ao tempo de secagem é preciso levar em consideração que a utilização de diferentes soluções com conteúdo químico pode prejudicar aspectos nutricionais dos produtos diminuindo teores de alguns parâmetros desejáveis, como o conteúdo de antioxidantes (CARRANZA-CONCHA et al, 2012).…”
Section: Introductionunclassified
“…Porém, além de notar-se o benefício da aplicação dessas substâncias com relação ao tempo de secagem é preciso levar em consideração que a utilização de diferentes soluções com conteúdo químico pode prejudicar aspectos nutricionais dos produtos diminuindo teores de alguns parâmetros desejáveis, como o conteúdo de antioxidantes (CARRANZA-CONCHA et al, 2012).…”
Section: Introductionunclassified